H-BN orientation degree on the thermal conductivity anisotropy of their silicone rubber composites: A quantitative study. (March 2023) - Song, Jinbao; Zhang, Kailun; Guo, Zihao; Liang, Tianqi; Chen, Chao; Liu, Jie; Shi, Dean
Abstract: The polymer-thermal conductive filler composite is a key to developing a high-efficiency thermal interfacial material (TIMs) for miniaturized electronic devices. Hexagonal boron nitride ( h- BN) is an attractive alternative for silicone rubber (SiR) based TIMs. However, their final distribution states are much more susceptible to the fabrication methods, thus significantly affecting the anisotropic thermal conductivity properties. Herein, we prepared three types of SiR-based TIMs with various h- BN orientations using the mechanical mixing (MM), hot-pressing (HP), and two-roll & hot-pressing (TR&HP) process, respectively. The effect of h- BN orientation degree on the anisotropy of thermal conductivity and interfacial thermal resistance of composites are investigated. The according effects on the hardness, ductility, and dielectric properties of composites are also illustrated. Our results indicate that in terms of h -BN filled SiR-based TIMs, the TR&HP process is recommended. The composites with highly oriented h -BN exhibit increased heat dissipation, tensile properties, and lower hardness.